Ethnomedicinal appraisal of plants used for the treatment of gastrointestinal complaints by tribal communities living in Diamir district, Western Himalayas, Pakistan. - Rahmat Wali; Muhammad Faraz Khan; Ansar Mahmood; Majid Mahmood; Rahmatullah Qureshi; Khawaja Shafique Ahmad; Zia-Ur-Rehman Mashwani (PLoS ONE, 2022)
Majority of the mountain dwelling communities living in the Himalayas rely on traditional herbal medicines for primary healthcare needs. Present study was conducted in fairy meadows and allied valleys in District Diamir, Gilgit Baltistan autonomous territory in northern Pakistan. Documentation of traditional medicinal knowledge (TMK) of local communities for the treatment of gastrointestinal disorders was carried out as a component of a wider medico-botanical expedition conducted in the entire base camp of the great Nanga Parbat peak during 2016-19. Various ethnobotanical parameters i.e. use value (UV), informant consensus factor (ICF), Fidelity level (FL), direct matrix ranking test (DMRT) and preference ranking (PR) were applied to evaluate the data collected during field surveys. The plants were also subjected to a comparative review for novelty assessment. A total of 61 medicinal plant species belonging to 55 genera and 35 families are reported here for the treatment of GIDs. Compositae was the leading family with 8 (13%) species. Fourteen gastrointestinal disorders were cured with 32% taxon were reported for stomachic followed by diarrhea (15%) and constipation (14%). Highest use reports (5) and use citations (207) were reported for Mentha longifolia L. while highest UV (1.79) was obtained for Artemisia maritima L. Hylotelephium telephioides (Ledeb.), A. maritima, M. longifolia, M. piperita L., Allium cepa L., and A. annua L. exhibited 100% FL. Highest ICF was calculated against dysentery and flatulence. DMRT ranked Prunus persica L. first for its multipurpose uses. Taking constipation as a reference gastrointestinal disease, PR for ten plant species was calculated where H. telephioides was ranked first followed by A. maritima. Present study concluded that 19 out of 61 plant species were documented for the first time with novel medicinal uses to cure GIDs. These plant species could act as potential reservoirs of novel lead compounds for the treatments of gastrointestinal disorders.